1978
DOI: 10.1111/j.1550-7408.1978.tb03905.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Infectivity and Concanavalin A Agglutinability of Algae Exsymbiotic from Paramecium bursaria

Abstract: SYNOPSIS. Eighteen strains of algae, including 17 exsymbiotic from Paramecium bursaria, were tested for infectivity for P. bursaria, syngen 2 aposymbiotes, and Concanavalin A (Con A) agglutinability. All 6 infective algal strains were relatively resistant to agglutination by Con A, suggesting that algal surface characteristics are correlated with infectivity. Among the noninfective strains, high and low agglutinability were about equally represented, indicating that the Con A titer alone is not a sufficient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
2

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
1
20
2
Order By: Relevance
“…In this regard, PBCV-1 is especially promising because several investigators (ref. 12 We thank Myron Brakke, Les Lane, and R. L. Pardy for many useful discussions and Ellen Ball for making antiserum to HVCV-1. This paper is published with the approval ofthe Director as paper no.…”
mentioning
confidence: 99%
“…In this regard, PBCV-1 is especially promising because several investigators (ref. 12 We thank Myron Brakke, Les Lane, and R. L. Pardy for many useful discussions and Ellen Ball for making antiserum to HVCV-1. This paper is published with the approval ofthe Director as paper no.…”
mentioning
confidence: 99%
“…Con A agglutination titers Jvrre detrrniincd on log-phase algae cultivated also for sugar release and infectivity studies. Details of the preparation of cell suspensions for Con X treatment \<ere described previously ( 14).…”
Section: Methodsmentioning
confidence: 99%
“…T h e present report is concerned with the possibility that specific sugar release by algae during their ingestion by an aposymbiotic ciliate may servr as a signal to the potential host resulting in the establishment of the algae as symbiotes. I n a previous report (14) a comparison was made between the response of symbiotic algae to the lectin Concanavalin A (Con A ) and the infectivity of the algae for aposymbiotic ciliates. It was found that infective algal strains were also relatively resistant to agglutination in the presence of Con A. Resistancr and sensitivity to agglutination were, however, about equally represented among the noninfective strains.…”
mentioning
confidence: 99%
“…The same is true for infective algae the surface of which has been coated by antibodies . Other experiments showed that chlorellae which are suitable for symbiosis formation are similar in Concanavalin A agglutinability, thus differing from unsuitable algae (WEIS 1978). Obviously infective algae are recognized by the Paramecium because of a special surface structure.…”
Section: Adaptive Features Of the Symbiotic Chlorella Specmentioning
confidence: 99%